Форми та методи визначення вартості лізингової операції - Черненко, В. І. (Ways to Improve Construction Efficiency, 2012)
The existing methods of calculating of the leasing payments are analyzed in the article. Specified common elements, and also shown the main differences and peculiarities. The main problems of existing methods were covered.